Bronchial thermoplasty and biological therapy as targeted treatments for severe uncontrolled asthma. Issue 7 (July 2016) - Trivedi, Abhaya; Pavord, Ian D; Castro, Mario
Summary: Although a small proportion of patients with asthma have severe disease, it accounts for the majority of morbidity related to the illness. Severe asthma comprises a heterogeneous group of phenotypes. Targeted treatments for these phenotypes represent a major advancement in the management of severe asthma. Omalizumab, a monoclonal antibody to IgE, improves asthma control in patients with a predominant allergic phenotype. Monoclonal antibodies targeted to interleukin 4α and interleukin 5 have shown substantial benefit in patients with the eosinophilic asthma phenotype; so too have monoclonal antibodies targeted to interleukin 13 in patients with a type 2 allergic phenotype. Bronchial thermoplasty, a new technique to reduce airway smooth muscle mass, improves symptoms and reduces exacerbations in patients with severe uncontrolled asthma and the chronic airflow obstruction phenotype. While awaiting comparative trials, we can now use a targeted approach with these phenotypes, guiding our treatment selection with the best evidence. This Review will focus on the latest developments in these new treatments and inform the clinician on how to select the appropriate patient for these treatments.